Design of a single dimension constrained vibratory finishing device - Muhammad Syahman Selamat. (2012)
Vibratory finishing is a process in which media particles or abrasives are set into vibratory motion in order to polish the desired surface of a work-piece. This project embarks on a new design and development of a vibratory finishing device which is capable of restricting the vibratory motion into a single direction of motion.